Exergy study of amine regeneration unit using diethanolamine in a refinery plant: A real start-up plant - Ahmed Y. Ibrahim; Fatma H. Ashour; Mamdouh A. Gadalla (Heliyon, 2021)
Refinery plants use diethanolamine (DEA) solutions for gas sweetening. The role of DEA is to absorb H2S from sour gas. Amine Regeneration Units (ARU) are used to regenerate the rich Amine with H2S from refinery units to Lean Amine. An ARU unit of a Middle Eastern refinery that began official production in 2020 was simulated using Aspen HYSYS V.11, and an exergy study was conducted on different equipment. Whereas energy is transformed from one form to another, the exergy is destroyed in an irreversible process. The total exergy was equal to the physical and chemical exergy. The physical exergy was calculated using HYSYS, and the chemical exergy was calculated using a series of equations embedded in Excel. The DEA concentration used was 25 wt%. The exergy destruction rates, destruction efficiency, and percentage share of destruction of each piece of equipment were calculated. The regenerator exhibited the highest destruction rate of 13459.73 kW, and a percentage share of 79.61% of the total destruction. The overall exergy efficiency was 99.7%. The DEA concentration decreased from 25% to 20% as a result of system losses during start-up. Therefore, a case study was conducted to test the effect of this decrease in the H2S concentration in the sweet gas, and no effect was observed. An exergy study was conducted using an DEA of 20%. The distribution of the equipment destruction did not change. The total destruction loss increased by 2057.08 kW. From the exergy and operation point of view, the best scenario was to use a 25% concentration, to prevent destruction losses and operation problems.